Toxicological impact of organic ultrafine particles (UFPs) in human bronchial epithelial BEAS-2B cells at air-liquid interface. (February 2022) - Juarez Facio, A.T.; Yon, J.; Corbière, C.; Rogez-Florent, T.; Castilla, C.; Lavanant, H.; Mignot, M.; Devouge-Boyer, C.; Logie, C.; Chevalier, L.; Vaugeois, J.-M.; Monteil, C.
Abstract: Air pollution has significant health effects worldwide, and airborne particles play a significant role in these effects. Ultrafine particles (UFPs) have an aerodynamic diameter of 0.1 μm or less, can penetrate deep into the respiratory tree, and are more toxic due to their large specific surface area, which should adsorb organic compounds. The aim of this study is to show the toxicological effects of UFPs with high organic content at low dose on BEAS-2B cells through at air-liquid interface (ALI) exposure using a Vitrocell® technology and a miniCAST (Combustion Aerosol Standard) generator. In conjunction with this approach, chemical analysis of particles and gas phase was performed to evaluate the presence of polycyclic aromatic hydrocarbons (PAHs). Chemical analyses confirmed the presence of PAHs in UFPs. With this experimental setup, exposure of the BEAS-2B cells induced neither cytotoxicity nor mitochondrial dysfunction. However, an increase of oxidative stress was observed, as assessed through Nrf2, NQO1, HO-1, CuZnSOD, MnSOD, and Catalase gene expression, together with significant induction of genes related to xenobiotic metabolism CYP1A1 and CYP1B1. Negative regulation of inflammatory genes expression ( IL-6 and IL-8 ) was present three hours after the exposition to the UFPs. Taken together, this experimental approach, using repeatable conditions, should help to clarify the mechanisms by which organic UFPs induce toxicological effects. Graphical abstract: Unlabelled Image Highlights: BEAS-2B cells were successfully exposed at ALI to primary UFPs emissions PAHs-rich UFPs induced an acute cellular toxicity at low exposed dose PAHs-rich UFPs activated oxidative stress and xenobiotic metabolism This methodological approach offers new perspectives to evaluate different kinds of UFPs